Analysis of The Suitability of Eleventh Grade Physics Textbooks with the Independent Curriculum - Erlina Puspita Wahyuningtyas; Ellianawati Ellianawati (UPEJ Unnes Physics Education Journal, 2023)
The emergence of the COVID-19 (Coronavirus Disease) pandemic in Indonesia at the end of 2019 became a turning point in all aspects of life, one of which was education which implemented a distance learning policy. This policy causes learning loss (loss of interest in learning) for some students. Efforts made by the government to overcome the problem of learning losses are by changing the curriculum. Learning resources in the form of subject text books used in schools are one of the learning media that has been affected by curriculum changes. The advantages and disadvantages of subject textbooks can be identified by conducting an analysis. This research was conducted with the aim of knowing the suitability of a physics textbook by authors Mike Crundell and Geoff Goodwin entitled